The Influence of Digital Media Use In Islamic Education Learning on Elementary Students' Motivation at SDIT Al-Barkah 03 - Syifa Fauziah; Padiah Achmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the impact of digital media use in Islamic Religious Education on students' learning motivation at SDIT Al-Barkah 03. With technological advancements, digital media is increasingly integrated into education, including in PAI lessons. The use of digital media is expected to attract interest and enhance students' motivation to learn, ultimately improving their understanding and engagement in PAI subjects. This research utilizes a quantitative approach utilizing a quasi-experimental design. The study sample consists of 60 participants. fourth and fifth-grade students, randomly selected from the student population at SDIT Al-Barkah 03. Data was collected through learning motivation questionnaires and observations of student engagement in lessons. The results indicate that the use of digital media in PAI has a positive and significant effect on students' learning motivation. Students who learned through digital media displayed higher enthusiasm, active participation in class discussions, and greater motivation to understand PAI material. Based on these findings, the utilization of digital media recommended as an effective instructional strategy to enhance student motivation and learning outcomes in PAI, especially at the elementary school level.